Seed pod shattering in the genus Lotus and its overcoming - Jana ŘEPKOVÁ; Jan HOFBAUER (Czech Journal of Genetics and Plant Breeding, 2009)
Birdsfoot trefoil (Lotus corniculatus L.) is a perennial species that is known for its outstanding characters as a crucial component of meadow and pasture vegetation and a highly successful fodder crop. However, its cultivation has been limited by the inability to control pod shattering. The anatomic and physiological bases of pod shattering are known and are considered to be controlled by more than one gene. This paper reviews the known causes of pod shattering and potential ways of overcoming pod indehiscence in L. corniculatus. Genetic transformation is possible in the genus Lotus; however, the useful genes determining the seed pod indehiscent character have not been identified yet. The only way of introducing pod indehiscence characters into L. corniculatus is by interspecific hybridization within the genus Lotus; embryo rescue and protoplast cultures are promising. To determine useful genotypes for crosses, investigations of pre- and post-fertilization barriers are necessary. To that end, we present here a convenient procedure for a whole-mount clearing treatment of immature seeds that leaves the cell walls of tissues intact. This is a useful technique for the study of post-fertilization barriers in Lotus.